Runoff and Soil Loss Studies of Treated Watersheds in Southern Rajasthan - A Case Study - Mittal, H K; Purohit, R C (Journal of Agricultural Engineering, 2006)
Unscientific exploitation and utilization of natural resources in India has resulted into environmental degradation. Watershed management programme is an ideal strategy for regeneration of such resources. Interim evaluation of the watershed management projects is possible through studies on runoff and soil loss. The present paper deals with such a study conducted in two watersheds namely Cheerwa and Losing of district Udaipur in southern Rajasthan. The runoff and sediment loss measurement was done at silt observations posts. The study has shown that in successive year, the runoff and soil loss has reduced to a reasonable extent and has shown good impact of various soil and water conservation measures.